PENGARUH PERENCANAAN, PENGORGANISASIAN, PELAKSANAAN DAN PENGAWASAN TERHADAP EFEKTIVITAS PELAYANAN RETRIBUSI PERSAMPAHAN DI KABUPATEN MAJALENGKA - Vidi Adhitama; Lalan Soeherlan Soekamta; Aceng Jarkasih (DIALOGIKA, 2022)
This research aims to analyze management functions including planning, organizing, implementation and supervision of its effect on service effectiveness. This research uses quantitative methods by testing hypotheses from the functions of planning, organizing, implementing and monitoring the effectiveness of services both simultaneously and partially. The sample in this study was employees involved in waste management at the Environment Agency which amounted to 142 using a random sampling system. The results of the study proved that planning, organizing, implementation and supervision have a positive influence on the effectiveness of services both simultaneously and partially